Character Values and Their Internalization in Teaching and Learning English at Madrasah - Islami, Milad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Language is more than to express the ideas, believe, and thought or as intellectual based, it also expresses the norms, values, and even emotions. As the result, it is important to internalize the character values into the teaching and learning activity of English. Since the focus of this study was on the analysis of the internalization of character values without any experimental or manipulated settings involved, the design of this study was qualitative. The results showed that there were at least six character values performed by the students in learning English, they were independent, hardworking ethos, curiosity, democratic attitude, communicative manner, and reading interest. In addition, the character values were internalized by the English teacher into the process of teaching and learning even though she did not realize it.